Hubungan Pola Konsumsi Asupan Natrium dengan Kejadian Preeklamsia Pada Ibu Hamil di Ruang VK Bersalin RSUD dr. Doris Sylvanus Palangka Raya - Eline Charla Sabatina Bingan; Aprilia Cahyaning Palupi (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2022)
Pregnant/delivery women with severe preeclampsia or eclampsia are a serious problem because they can threaten death for both the mother and the fetus. Preeclampsia is the second leading cause of death in pregnancy in the world. In Indonesia, the cause of death ranges from 1.5% to 25%. At dr. Doris Sylvanus Palangka Raya there was an increase in the number of mothers with preeclampsia from 2018 as many as 259 to 2019 as many as 277 cases or an increase of 3.35%. Fulfillment of increased intake of balanced food plays an important role in the health of pregnant women and the fetus. This happens because of unhealthy living habits with the habit of consuming foods that are high in fat, high in salt and little protein. This study aims to determine the relationship between consumption patterns of sodium intake and the incidence of preeclampsia in pregnant women in the VK delivery room at RSUD dr. Doris Sylvanus Palangka Raya. This type of research is analytic observational, with a cross sectional design. The sampling technique used purposive sampling, the samples in this study were pregnant women in January-March 2020. The results of the Chi-Square Test analysis obtained a value of ρ = 0.014 <α 0.05, this proves that there is an influence between the independent variables and the dependent variable with OR = 6.314. There is a relationship between consumption patterns of sodium intake and the incidence of preeclampsia in pregnant women in the maternity ward of RSUD Dr. Doris Sylvanus Palangka Raya.